2013
DOI: 10.1107/s1600536813013470
|View full text |Cite
|
Sign up to set email alerts
|

Bis[μ-1,3-bis(diphenylphosphanyl)propane-κ2P:P′]digold(I) tetrachloridonickelate(II) diethyl ether monosolvate

Abstract: The title compound, [Au2(C27H26P2)2][NiCl4]·C4H10O, consists of a digold(I) complex cation, an [NiCl4]2− complex anion and a diethyl ether solvent mol­ecule. Two 1,3-bis­(di­phenyl­phosphan­yl)propane (dppp) ligands bridge two AuI atoms, forming a metallacycle in which each of the AuI atoms is coordinated in a slightly distorted linear environment by two P atoms. In the complex anion, the NiII atom is coordinated by four chloride ligands in a distorted tetra­hedral geometry. The complex cation and the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…2,7,14,[33][34][35] The phosphorus atoms of both phosphanes in the complexes possess a tetrahedral environment. The Au-P bond lengths, which vary from 2.29(11) to 2.33(12) Å for the complexes, are similar to those reported for the analogous compounds; 2,7,14,33-37 for example, 2.3013(13)-2.3129(13 36 However, these distances are relatively shorter than in the tetrahedrally coordinated complex, [Au(Dppp)(PPh 3 )Cl] (2.39(13) Å). 38 The Au-P bond lengths in complex 4 are comparatively shorter owing to the electron donating nature of diphosphane.…”
Section: X-ray Structures Of Complexes 1 2 Andsupporting
confidence: 78%
See 1 more Smart Citation
“…2,7,14,[33][34][35] The phosphorus atoms of both phosphanes in the complexes possess a tetrahedral environment. The Au-P bond lengths, which vary from 2.29(11) to 2.33(12) Å for the complexes, are similar to those reported for the analogous compounds; 2,7,14,33-37 for example, 2.3013(13)-2.3129(13 36 However, these distances are relatively shorter than in the tetrahedrally coordinated complex, [Au(Dppp)(PPh 3 )Cl] (2.39(13) Å). 38 The Au-P bond lengths in complex 4 are comparatively shorter owing to the electron donating nature of diphosphane.…”
Section: X-ray Structures Of Complexes 1 2 Andsupporting
confidence: 78%
“…12 Accumulating evidence demonstrates that in addition to the bidentate chelating mode in gold(I) complexes, [31][32][33] diphosphanes have been intensely applied as bridging ligands in the formation of polymeric chains and macrocyclic complexes. 2,31,[33][34][35][36] However, the selective formation of mixed phosphane (containing both mono-and diphosphane) gold(I) complexes remains largely unexplored. Caruso et al reported the antitumor activity of the mixed phosphane gold species containing triphenylphosphane (PPh 3 ), and 1,2-bis(diphenylphosphano)ethane (Dppe) and 1,3-bis(diphenylphosphano)propane (Dppp).…”
Section: Introductionmentioning
confidence: 99%
“…Au4 and Au9 (auranofin) are purchased from Sigma-Aldrich. Au1–Au3 ( Hickey et al, 2008 ; Long et al, 2021 ), four dinuclear gold(I)-phosphine compounds Au5–Au8 ( Che et al, 1990 ; Fu et al, 1999 ; Igashira-Kamiyama et al, 2013 ; Zou et al, 2014 ) and two auranofin derivatives Au10–Au11 ( Baker et al, 2005 ) were synthesized and characterized as previously described.…”
Section: Methodsmentioning
confidence: 99%